George Pachymeres' gnoseological system and his inductive method in the "Paraphrase" of "De divinis nominibus" of Dionysius the Areopagite - Petridou, Lydia; Terezēs, Chrēstos Ath. ca. 20./21. Jh. (2015)
This study deals both with the gnoseological system of the byzantine theologian George Pachymeres, which is constructed on the methods of the affirmative, negative and superlative theology and the inductive method that he follows at his Paraphrase of De divinus nominibus of Dionysius the Areopagite, in order general conclusions on causality to be expressed. In the context of a consistent ontological monism, G. Pachymeres, without violating the epistemological approach of the Supreme Principle as Unknown, categorizes the sensible facts according to the similarities and the differences between them, so as to present God as the only cause of the produced world.